EDITOR'S NOTE VERBA VOLAT, SCRIPTA NAMENT (The word is fleeting, writings are permanent). - Guy Straus, Lawrence (Journal of Anthropological Research)
An introduction is presented in which the editor reflects on the importance of publication as a form of anthropological preservation of the written word, despite modern technology, and discusses aspects of publishing the periodical.